La résistance comme transmission et amour de l’héritage - Janine Altounian (Amnis)
Taking as an example the Journal de deportation written by a survivor of the 1915 Armenian genocide, we aim at showing how tightly a man’s power of resistance is bound to his unconditional attachment to the values and precepts handed down from his culture and his ancestors. This hypothesis will be discussed with regard to the contents of the Journal as well as its posthumous fortune.